2017
DOI: 10.1002/hyp.11126
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal patterns of major ions in urban stormwater under cold climate

Abstract: Multiple natural and anthropogenic factors affect urban water chemistry. However, little is known about the abundance or temporal variation of major ions in urban runoff. This study explores the spatio‐temporal variation of major dissolved ions (Na, K, Ca, Mg, Cl, NO3, and SO4) and total dissolved solids (TDS) in cold climate urban stormwater. Three watersheds with varying degrees of urban land use intensity and imperviousness (from 36% to 66%) in Helsinki, Finland, were continuously monitored for 5 years usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 88 publications
6
20
0
Order By: Relevance
“…At least four studies focused on thermal and/or salt loads transported by urban runoff. Although salts are likely to follow strong seasonal patterns, with the highest export in the spring following wash-off of winter deicing chemicals, Taka et al (2017) reported chronically elevated salt concentrations across three urban watersheds in Finland. In this study, Cland Na + were linked to winter deicing activities, while Ca 2+ , K + and Mg 2+ were likely associated with weathering of other urban surfaces.…”
Section: Mccarthy Et Al (2017) Demonstrated a Microbial Sourcementioning
confidence: 98%
“…At least four studies focused on thermal and/or salt loads transported by urban runoff. Although salts are likely to follow strong seasonal patterns, with the highest export in the spring following wash-off of winter deicing chemicals, Taka et al (2017) reported chronically elevated salt concentrations across three urban watersheds in Finland. In this study, Cland Na + were linked to winter deicing activities, while Ca 2+ , K + and Mg 2+ were likely associated with weathering of other urban surfaces.…”
Section: Mccarthy Et Al (2017) Demonstrated a Microbial Sourcementioning
confidence: 98%
“…For quality assurance and quality control, the external standard method was used for quantitative analysis based on six-point calibration (1,2,4,6,8, and 10 μg ml −1 ). e linear regression coefficients for cholesterol, cholestanol, coprostanol, epicoprostanol, campesterol, sitosterol, and stigmasterol were 0.989, 0.979, 0.977, 0.986, 0.941, 0.992, and 2…”
Section: Sterols Analysismentioning
confidence: 99%
“…With strict industrial pollution control, domestic sewage discharge has increasingly become the main concern of water quality issues in many populated regions [1][2][3][4]. Sterols have been widely used as a typical biochemical marker to indicate the source of organic matter, such as domestic sewage, marine, and terrestrial source [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic land use, comprising agriculture, development and urbanization, contributes to increased nutrient and ion concentrations (Taka et al. ), pollutants and turbidity (due to sediment load) in streams (Foley et al. ), and these effects cascade downstream (Levesque et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, land cover previously dominated by agriculture may sustain high nutrient loads from sediments to streams for a long time period after a change in land use (Maloney and Weller 2011). Anthropogenic land use, comprising agriculture, development and urbanization, contributes to increased nutrient and ion concentrations (Taka et al 2017), pollutants and turbidity (due to sediment load) in streams (Foley et al 2005), and these effects cascade downstream (Levesque et al 2017). Wang et al (2008) found that nutrient loading and percent of urban land use were the most important drivers of deteriorating stream conditions.…”
Section: Introductionmentioning
confidence: 99%